Colorectal cancer screening in patients with spinal cord injury yields similar results to the general population with an effective bowel preparation: a retrospective chart audit. Issue 3 (March 2018) - Teng, Brandon; Song, Shawn; Svircev, Jelena; Dominitz, Jason; Burns, Stephen
Abstract Study design Retrospective chart audit. Objectives To compare adequacy of colonoscopy bowel preparation and diagnostic findings between persons with SCI receiving an extended inpatient bowel preparation and the general population. Setting Veterans Affairs Puget Sound Healthcare System, Seattle, WA, USA. Methods We reviewed an electronic database of all colonoscopies performed at a tertiary Veterans Affairs medical center between 7/12/13 and 15/10/15. Patients with SCI received a multi-day bowel preparation with magnesium citrate, and 8–10 liters of polyethylene glycol-3350 and electrolyte colonic lavage solution (PEG-ELS) over two and one half days. The control population received a standard bowel preparation consisting of magnesium citrate and 4 liters of PEG-ELS over 1 day. Results Two hundred and fifty-five patients were included in the study, including 85 patients with SCI. Average risk screening was a more common colonoscopy indication in patients with SCI vs. the control population (24 vs. 13%p = 0.03). There was no difference in adequacy of bowel preparation (87 vs. 85%, p = 0.73) or adenoma detection rate (55 vs. 51%, p = 0.59) when comparing patients with SCI with the control population. No difference in polyp histopathology was detected (p = 0.748). Conclusions Our study demonstrated that an extended bowel preparation for patients with SCI produces similar bowel preparation results and diagnostic yield when compared to patients without SCI undergoing colonoscopy.